2001
DOI: 10.1097/00006842-200109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Employee Effects of an Educational Program for Managers at an Insurance Company

Abstract: The study indicates that a moderately intensive psychosocial manager program lasting for 1 year can be beneficial for the employees with regard to both lowered serum cortisol and improved authority over decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 24 publications
7
75
1
5
Order By: Relevance
“…These results showed an improvement in three of the four psychosocial work factors (high PD, low co-workers SS and low reward). These results are consistent with those of previous prospective intervention studies that observed an improvement in at least one psychosocial work factor (Anderzen and Arnetz 2005;Bourbonnais et al 2006;Kauffeld et al 2004;Logan and Ganster 2005;Mikkelsen and Gundersen 2003;Mikkelsen et al 2000;Sluiter et al 2005;Theorell et al 2001;Wahlstedt et al 2000). It is noteworthy that, in our study, only the respect and esteem dimension of reward improved.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results showed an improvement in three of the four psychosocial work factors (high PD, low co-workers SS and low reward). These results are consistent with those of previous prospective intervention studies that observed an improvement in at least one psychosocial work factor (Anderzen and Arnetz 2005;Bourbonnais et al 2006;Kauffeld et al 2004;Logan and Ganster 2005;Mikkelsen and Gundersen 2003;Mikkelsen et al 2000;Sluiter et al 2005;Theorell et al 2001;Wahlstedt et al 2000). It is noteworthy that, in our study, only the respect and esteem dimension of reward improved.…”
Section: Discussionsupporting
confidence: 93%
“…Follow-up time was not long enough to allow the effects of the intervention to occur. Indeed, most recent studies evaluated the effects on health outcomes one year or less after the implementation of the intervention (Anderzen and Arnetz 2005;Berkhout et al 2004;Bond and Bunce 2001;Bourbonnais et al 2006;Eklof and Hagberg 2006;Fredriksson et al 2001;Jackson and Mallarky 2000;Kawakami et al 2005;Michie et al 2004;Mikkelsen and Gundersen 2003;Mikkelsen et al 2000;Park et al 2004;Parker 2003;Ryan et al 2005;Sluiter et al 2005;Theorell et al 2001;Wahlstedt et al 2000). An appropriate follow-up requires that sufficient time elapse since the implementation of the intervention to produce a meaningful decrease in adverse work factors and consequent improvement in health outcomes.…”
Section: Job Controlmentioning
confidence: 99%
“…Of those, seven controlled studies that met the inclusion criteria were selected [5][6][7][8][9][10][11] (Tables 1 and 2). For the discussion of the content and types of training, five additional studies were included 1,[12][13][14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
“…Immediately after and 6 mo after the training, the rate of insomnia significantly increased in the nurses of the pay-cut hospital, but the increase in insomnia complaints was suppressed in the nurses working under the supervisors who received the training 9) . Supervisors in an insurance company received education to enhance their managing ability, so as to improve the psychosocial occupational environment, for 2 h every other week for 1 yr (60 h in total) 10) . The training on the 3) Managers in an information technology company were randomly assigned to an intervention group (n=9) or control group (n=7), and their 92 and 84 subordinates, respectively, were compared.…”
Section: Summary Of Retrieved Literature: Quasi-experimental Studies mentioning
confidence: 99%
“…Selain itu juga dapat dinilai menggunakan beberapa paramater lain (misalnya self efficacy, stresor dan distres psikologi dari kuesioner BJSQ, kuesioner Nordic Body Map dan keluhan muskulo-skeletal/fisik lainnya, dan beberapa marker biologi dari pemeriksaan darah/urin/saliva) (Theorell, Emdad, Arnetz, & Weingarten, 2001;Appels & Kop, 2007;Bellingrat, Weigl, & Kudielka, 2009;Maina, Bovenzi, Palmas, & Filon 2009;Den, Toda, Ohira, & Kanehisa, 2011). Agar lebih akurat pengukuranpengukuran efektivitas program sebaiknya dilakukan sebelum dan sesudah pelaksanaan program.…”
Section: Acuan-acuan Dalam Melaksanakan Program Manajemen Stres Kerjaunclassified